Genetic diversity analysis of agro-morphological and quality traits in populations of sainfoin (Onobrychis sativa) - Mohajer, S.; Jafari, A.A.; Taha, R.M.; Yaacob, J.S.; Saleh, A. (2013)
In order to study the variations and relations among morphological and quality traits, 12 populations (accessions) of sainfoin (Onobrychis sativa), were assessed under sward growth condition using split plot design with two replications for three years. In this regard, each variety was cultivated in plot area directly and different traits were assessed when 50 of plants produced flowers. Results of combined analyses showed that there were significant differences among 3 years for all of traits except plant density. Based on these results, the average values of 6.47 and 10.31 ton ha-1 dry matter (DM) yield were obtained in the first and second year, respectively. Phenotypic correlation between DM yield with both dry matter digestibility (0.35*) and crude fiber (0.58*) were positive, whereas its relationship with crude protein (CP) was negative (-0.82**). Using principal component analysis, the first four independent components with values more than 1.0 accounted for 88 of total variation, namely plant density, forage quality, seed yield and dry matter yield component. Based on Ward cluster analysis method, 12 populations were divided into 3 groups. Ultimately, superior populations were identified to improve the breeding of sainfoin in terms of high quality and forage yield coupled with resistance to powdery mildew disease.